English Language Learning Anxieties of Last-Mile Learners As A Basis for Developing The V.O.I.C.E. Framework - Sonny Villamor; Rennie C. Saranza (Journal of English Language and Pedagogy (JELPA), 2025)
Anxiety is a significant factor affecting learners' language performance. Hence, this study aimed to explore the anxieties that last-mile learners experienced when learning English using a phenomenological approach to qualitative research. Eight Grade 7 participants were selected through purposive and convenience sampling for in-depth interviews, given their accessibility and availability within the school setting. Thematic analysis was employed to analyze the data collected. Findings revealed that last-mile learners experienced both positive and negative aspects of English language learning. The negative aspects included inadequate English language proficiency, fear of making mistakes, inability to answer questions, and fear of embarrassment, particularly during speaking tasks and assessments. To cope with these, learners employed various strategies, such as emotional regulation, seeking social support from peers and teachers, and engaging in academic practices like self-study and repetition. In response to the findings, the V.O.I.C.E. Framework was developed to address English language learning anxiety. The study recommends that English instruction be made more interactive, inclusive, and learner-centered to reduce anxiety and enhance student engagement. Future research is encouraged to examine this phenomenon further to uncover deeper insights and inform effective educational interventions.